Development of thermal barrier coating on tool steel surface - Nur Adilah, Ahmad (2013)
In hot forming process, die surface tends to wear when experienced cyclic high working temperature. Among the technique to overcome die failure after thousands of cycle, is to develop a thermal barrier system on the die surface. This project focused on development of ceramic coating on H13 tool steel surface at different parameters to achieve a good quality of coating characteristics. Yttria Stabilized Zirconia (YSZ) was used as the coating powder of top coat layer and Praxair Plasma Spray system with SG-100 gun was used to deposit coating materials on substrate surface. The design was optimized for maximum hardness. The microscopy finding indicated variation of coating thickness at different parameters settings. The highest hardness obtained is 435 HV0.1 from sample with optimum parameter at lower powder feed rate and higher of input current and stand-off distance. YSZ thermal barrier coating process increased the surface hardness considerably.